2021
DOI: 10.1177/15593258211040329
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hyperuricemic and Uricosuric Potential of Berberis vulgaris in Oxonate-Induced Hyperuricemic Rats

Abstract: Hyperuricemia is a metabolic disorder with characteristic elevated serum uric acid. Recently, several plant-based medicines are being used for the treatment of hyperuricemia. The study aimed to find the hypouricemic potential of Berberis vulgaris in in-vitro and in-vivo study models. In i n-vitro studies, xanthine oxidase inhibition assay was performed to evaluate IC50 value and capsule absorbance of the drug, respectively. For in-vivo experiment, the study comprised 15 groups of rats. In-vitro results reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It could be presumed that drugs extracted from this herb may be more beneficial with lesser adverse effects. 25 A limitation of the present study was the time course of treatment: treatment is initiated before the disease pathology is initiated (prophylactic treatment). Drug accumulation is a prerequisite for the desired therapeutic effect.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It could be presumed that drugs extracted from this herb may be more beneficial with lesser adverse effects. 25 A limitation of the present study was the time course of treatment: treatment is initiated before the disease pathology is initiated (prophylactic treatment). Drug accumulation is a prerequisite for the desired therapeutic effect.…”
Section: Resultsmentioning
confidence: 98%
“…It could be presumed that drugs extracted from this herb may be more beneficial with lesser adverse effects. 25…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that there was XO inhibition with a significant decrease of serum and liver uric acid levels significantly in a dose‐ and time‐dependent manner. In addition, 3‐day and 7‐day administration of B. vulgaris showed more potential compared to 1‐day administrations (Bilal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%